2021
DOI: 10.1002/anie.202015680
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Di‐tert‐butyldiphosphatetrahedrane: Access to (tBuCP)n (n=2, 4) Ligand Frameworks by P−C Bond Cleavage

Abstract: The first mixed phosphatetrahedranes were reported only recently and their reactivity is virtually unexplored. Herein, we present a reactivity study on di‐tert‐butyldiphosphatetrahedrane (1), which is the dimer of tert‐butylphosphaalkyne. The (tBuCP)2 tetrahedron is activated selectively by N‐heterocyclic carbene (NHC) nickel(I) and nickel(0) complexes, resulting in novel complexes featuring diverse (tBuCP)n‐frameworks (n=2, 4). Release of the (tBuCP)4 framework from one of the complexes was achieved by additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Thus, reactions with anionic metalates of Fe and Co afforded η 4 ‐coordinated diphosphacyclobutadiene complexes [10a] . Similar diphosphacyclobutenediide ligands were formed when reacting ( t BuCP) 2 with Ni(0) and Ni(I) NHC complexes, showing planar t Bu 2 C 2 P 2 2− units which are σ‐coordinated to Ni atoms [10c] . Only two complexes with intact phosphatetrahedrane moieties have been structurally characterized so far.…”
Section: Figurementioning
confidence: 98%
“…Thus, reactions with anionic metalates of Fe and Co afforded η 4 ‐coordinated diphosphacyclobutadiene complexes [10a] . Similar diphosphacyclobutenediide ligands were formed when reacting ( t BuCP) 2 with Ni(0) and Ni(I) NHC complexes, showing planar t Bu 2 C 2 P 2 2− units which are σ‐coordinated to Ni atoms [10c] . Only two complexes with intact phosphatetrahedrane moieties have been structurally characterized so far.…”
Section: Figurementioning
confidence: 98%
“…Molekülstrukturen von 2 (links), 3 a (Mitte) und 3 b (rechts) im Festkçrper. [19] Die Schwingungsellipsoide entsprechen einer Aufenthaltswahrscheinlichkeit von 50 %. Bei 2 ist nur ein Molekül der asymmetrischen Einheit gezeigt.…”
Section: àunclassified
“…Dimerisierung von 1 in der Koordinationssphäre von [(IMes) 2 Ni] (oben) und Molekülstruktur von 4 im Festkçrper (unten). [19] Die Schwingungsellipsoide entsprechen einer Aufenthaltswahrscheinlichkeit von 50 %. Wasserstoffatome und Lçsungsmittelmoleküle und eine fehlgeordnete Komponente (P2B und P3B) sind nicht gezeigt.…”
Section: Zuschriftenunclassified
“…6,7 This has inspired the study of the reaction chemistry of A-C, which has revealed some similarities, but also differences with respect to the chemistry of white phosphorus in particular. [3][4][5][8][9][10][11][12][13][14] Isomerisations of the phosphatetrahedrane scaffold have been observed in reactions with main group nucleophiles. Thus, N-heterocyclic carbenes (NHCs) effect P-C or P-P bond cleavage in A, giving bis( phosphaalkenes) or phosphirenes depending on the NHC (Fig.…”
Section: Introductionmentioning
confidence: 99%